The Presentation of The Cases With Intracranial Bleeding Due To Late Hemorrhagic Disease of The Newborn (Annals of Medical Research, 2021)
None
Keywords: Vitamin K, Late hemorrhagic disease of the newborn, Intracranial hemorrhagia, Prophylaxis.